Analisis Akuntabilitas dan Transparansi Keuangan PSSI dalam Perspektif Hukum Organisasi Nirlaba - Ilhan Pasha Islamy Trisnadi; Ariawan Gunadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Indonesian Football Association (PSSI), as a nonprofit legal entity, holds a central role in the development of national football. Its funding, derived from public sources, sponsorships, broadcasting rights, and government assistance, demands a financial management system rooted in transparency and accountability. This study aims to examine the extent of PSSI’s financial responsibility and compare its practices to international standards, particularly those set by FIFA. A normative legal research method was applied, utilizing literature reviews and analysis of relevant regulations, including Law No. 3 of 2005 on the National Sports System. The findings indicate that while PSSI has initiated reforms through independent audits conducted by Ernst & Young and the establishment of a Financial Transparency Task Force, public access to financial records remains limited, and the organization has yet to fully adopt integrated digital accounting systems. To enhance governance quality, there is a need for stronger institutional commitment, consistent external oversight, and active public participation as a form of social control